2013
DOI: 10.1590/s1413-35552012005000073
|View full text |Cite
|
Sign up to set email alerts
|

COPD patients' oxygen uptake and heart rate on-kinetics at cycle-ergometer: correlation with their predictors of severity

Abstract: | Objectives: To assess whether there is a correlation between oxygen uptake (VO 2 ) and heart rate (HR) on-kinetics in the constant-load cycle-ergometer test (CLT) and the BODE index and its isolated variables in patients with chronic obstructive pulmonary disease (COPD). Method: Fourteen male patients between 55 and 78 years of age with moderate to severe COPD were evaluated. Each patient underwent spirometry, the six-minute walk test (6MWT), the cycle-ergometer incremental test (IT) and CLT on alternate day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
1
6
1
1
Order By: Relevance
“…Studies have demonstrated a strong correlation between FEV1 and the 6-MWT, which is a predictor of exercise capacity (Ijiri et al 2014), suggesting that patients with peripheral and respiratory muscle weakness have reduced exercise capacity (Singer et al 2011). In the present study, this response was dependent upon inspiratory muscle strength (r = have a low O2 pulse is consistent with the notion that expiratory flow limitation contributes to hyperinflation during exercise, limiting the increase in stroke volume and, potentially, O2 delivery (Pessoa et al 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Studies have demonstrated a strong correlation between FEV1 and the 6-MWT, which is a predictor of exercise capacity (Ijiri et al 2014), suggesting that patients with peripheral and respiratory muscle weakness have reduced exercise capacity (Singer et al 2011). In the present study, this response was dependent upon inspiratory muscle strength (r = have a low O2 pulse is consistent with the notion that expiratory flow limitation contributes to hyperinflation during exercise, limiting the increase in stroke volume and, potentially, O2 delivery (Pessoa et al 2013).…”
Section: Discussionsupporting
confidence: 88%
“…19,20 However, such quick tests do not reflect cardiorespiratory capacity, especially as _ VO 2 kinetics are known to be slowed and related to the severity of the respiratory disease. 21,22 For patients with NSCLC, a longer evaluation over 3 minutes seems more appropriate since respiratory function is often altered and it may take 3 minutes for cardiorespiratory function to adapt to a constant load test.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this was due to the significantly shorter duration of the incremental phase: 4.3±1.7 minutes for the 15-watt/min group, versus 5.7± 2.0 minutes for the 10-watt/min group. This duration may not have allowed adequate physiological adaptation in this cohort of older individuals with respiratory comorbidities and reduced V O 2 kinetics (24,25). Furthermore, less than 10% of patients exceeded a power of 120 watts and so the risk of prolonging the effort disproportionately with increments of 5 to 10 watts is very low, since the maximal expected power for a CPET with an increment of 15 watts per minute is about 150 watts.…”
Section: Low-intensity Incremental Protocols To Increase the Duration Of The Cpetmentioning
confidence: 94%